Decision on Multiplier Grant to Ukraine: April 2023 - Global Partnership for Education (2023)
The Board of Directors approved a $25.55 million grant from the GPE Multiplier to Ukraine as accelerated financing.
KerkoCite.ItemAlsoKnownAs: 2339240:DGFF77EH 2405685:94H3QKU2

Guidelines for Accelerated Funding - Global Partnership for Education (2023)
These guidelines describe the criteria for eligibility, amount, eligible activities and duration of accelerated funding from GPE.
KerkoCite.ItemAlsoKnownAs: 2339240:LQLLE5W9 2405685:NIKFTMA8

Education in Ukraine - Global Partnership for Education (2022)
Learn more about Ukraine's education objectives and strategy, view grant information and education data, and explore the results and progress made.
KerkoCite.ItemAlsoKnownAs: 2339240:IDSHWHRD 2405685:FRI4SD5H

Education in Ukraine: Over $51 million in grants and in-kind support announced from GPE, Google and Microsoft - Global Partnership for Education (2023)
As the war continues in Ukraine, severely disrupting education, GPE, Google, Microsoft Corporation and UNESCO will provide over US$51 million for distance learning and psychosocial support for children in conflict-affected areas. The program will be rolled out by UNESCO and UNICEF in Ukraine in partnership with the Ministry of Education and Science of Ukraine.
KerkoCite.ItemAlsoKnownAs: 2339240:DXGPR83S 2405685:R73YDTKY

Ukraine: Education brings mental health support to children - Global Partnership for Education (2025)
Read how GPE and partners are helping increase the capacity of Ukraine’s educators to provide children with mental health services.
KerkoCite.ItemAlsoKnownAs: 2339240:D3G3B248 2405685:N7KZDHL6

Accelerated Funding Grant Progress Report - Global Partnership for Education (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:VPX89MS5 2405685:B5S8KK2E

Approval of Multiplier Grant to Ukraine as Accelerated Funding - Global Partnership for Education (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:MBY5PT68 2405685:AR2K4ZK2

Guidelines: System Capacity Grant - Global Partnership for Education (2024)
KerkoCite.ItemAlsoKnownAs: 2339240:Z9XVIP5P 2405685:P5HB9YH3

Achieving gender equality in and through education - Global Partnership for Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:PJLSZJIL 2405685:MYN2NRGK

Education in Sierra Leone | Where We Work | Global Partnership for Education - Global Partnership for Education (2007)
Learn more about education in Sierra Leone, view grant information and education data, and explore the results and progress made by the country.
KerkoCite.ItemAlsoKnownAs: 2339240:52XRRPXI 2405685:R9K2NZAQ

GPE's Engagement on Domestic Financing for Education - Global Partnership for Education (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:LWBNM2DF 2405685:RGL6677R

Education in Madagascar - Global Partnership for Education (2020)
See education data for Madagascar and learn about GPE programs, grants, results and progress.
Library Catalog: www.globalpartnership.org KerkoCite.ItemAlsoKnownAs: 2405685:R6YB53TI 2405685:ZZXJ6FCV

Senegal - Global Partnership for Education
KerkoCite.ItemAlsoKnownAs: 2339240:PJQUD9F9 2405685:Q5R45MCK

Education in Tanzania - Global Partnership for Education (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:KJIAJ4F2 2405685:N4Z4I5X6

Pakistan (Balochistan): Using technology to bring education to the most remote areas - Global Partnership for Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:X8TQADM6 2405685:8C795EZ9

Education in Yemen - Global Partnership for Education (2020)
See education data for Yemen and learn about GPE programs, grants, results and progress.
Library Catalog: www.globalpartnership.org KerkoCite.ItemAlsoKnownAs: 2339240:26KW8YWN 2405685:FBLWX9MK 4803016:BZ2NFKYX

Programa de Educação em Emergência 2020-2021 financiado pela Parceria Global da Educação - Global Partnership for Education (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:PNVVS63J 2405685:WKLCL6TG

Proposal for GPE Accelerated Funding for COVID-19 Response (Malawi) - Global Partnership for Education (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:FJXR8BZE 2405685:64GPW6ZN

Zambia COVID-19 Accelerated Funding Application Form - Global Partnership for Education (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:V3C72JI3 2405685:QZAE7YL8

Global Partnership for Education provides $68 million in grants for education response to COVID-19 (coronavirus) - Global Partnership for Education (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:LEZDGE4T 2405685:CYHEM8QR

Grant request to finance Rwanda COVID-19 education response from COVID-19 accelerated funding window under the GPE fund - Global Partnership for Education (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:LFVAFBW8 2405685:YT65AH7X

Ghana COVID-19 Accelerated Funding Application Form - Global Partnership for Education (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:X4EJC59Z 2405685:7DBZ64LJ

3 examples of mother tongue education to improve learning | Blog | Global Partnership for Education - Global Partnership for Education (Education for All blog, 2019)
GPE supports mother tongue education as a key component of the foundation of learning. On International Mother Tongue Day we review how three partner countries—Eritrea, The Gambia and Uzbekistan—with help from GPE, are implementing mother tongue programs.
KerkoCite.ItemAlsoKnownAs: 2339240:BDTJKNV3 2405685:NKEBMREJ

Cover Note for COVID-19 Accelerated Funding Request - Global Partnership for Education (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:6J3QVH7N 2405685:76CTU2H2

Sierra Leone: The power of great teaching in times of crisis | Stories of change - Global Partnership for Education
The Ebola crisis that plagued Sierra Leone in 2014-2016 had an unexpected positive consequence: giving learners access to the country’s best teachers through an innovative radio educational program. This experience served the country well when the COVID-19 pandemic hit.
KerkoCite.ItemAlsoKnownAs: 2339240:FF2WVB22 2405685:5IUL2ZH8

KENYA GPE COVID 19 Learning Continuity in Basic Education Project - Global Partnership for Education (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:AQPAEQP5 2405685:GR8UTH9R

Global Partnership for Education - Global Partnership for Education (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:K2UK6QF4 2405685:XTNVEKFL

Global Partnership for Education launches new public-private initiative to address the data challenge in global education - Global Partnership for Education (Global Partnership for Education, 2018)
In an effort to help developing countries strengthen their collection, management and utilization of education data, high-level representatives from the private sector, international organizations, developing country governments and other partners are coming together at the Global Partnership for Education (GPE) Financing Conference to launch a major new initiative called the Education Data Solutions Roundtable.
KerkoCite.ItemAlsoKnownAs: 2339240:TKZR8775 2405685:P6NCTW32

Education in Pakistan - Global Partnership for Education (Global Partnership for Education, 2021)
See education data for Pakistan and learn about GPE programs, grants, results and progress.
KerkoCite.ItemAlsoKnownAs: 2339240:ZEWKSVKM 2405685:DXUGPUV7

Cover note for COVID-19 accelerated funding request - Global Partnership for Education (Global Partnership for Education, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:SC59K4ZJ 2405685:WBAZV7WY

Education in Tanzania - Global Partnership for Education (Global Partnership for Education website, 2021)
See education data for Tanzania and learn about GPE programs, grants, results and progress.
KerkoCite.ItemAlsoKnownAs: 2339240:4K7E29Y5 2405685:EFXBWES9

Using technology to bring education to the most remote areas - Global Partnership for Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:CV6J6IEN 2405685:Q6H4DRVL

Application and program document for COVID-19 accelerated funding for Kenya - Global Partnership for Education (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:AGYR5NT4 2405685:L3FWL7A2

Kenya Partnership Compact. 2021 | Documents | Global Partnership for Education - Global Partnership for Education (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:TZEUP59V 2405685:FABDEDV3

Data Must Speak about Positive Deviance Approaches to Learning - Global Partnership for Education (GPEKIX)
KerkoCite.ItemAlsoKnownAs: 2339240:JNNRWNDW 2405685:J8PKUJ2X
Keywords: ⛔ No INSPIRE recid found

Cover Note for Lao PDR COVID-19 Accelerated Funding Request - Global Partnership for Education (Global Partnership for Education, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:SH8JUF4B 2405685:4TI9HG5B

GPE 2025 Results Framework for Lao PDR - Global Partnership for Education (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:XHMG8A45 2405685:LX7QPQDY
Keywords: ⛔ No INSPIRE recid found

Coordinated Action to Transform Education: What's in it for ministries of education - Global Partnership for Education (2023)
By leading and working through coordination bodies, ministries of education can mobilize smarter partnerships, ensure continued commitments to collective action and generate evidence for policy making, learning and adaptation.
KerkoCite.ItemAlsoKnownAs: 2339240:UH2Z3HED 2405685:3XCYIH9K

Guidelines for Education Sector Plan Preparation - Global Partnership for Education (GPE) (2015)
KerkoCite.ItemAlsoKnownAs: 2339240:JHGE3N95 2405685:NCTRWAZ7

Education sector analysis methodological guidelines - UNESCO-IIEP; World Bank; UNICEF; Global Partnership for Education (2014)
The Methodological Guidelines provide methods for carrying out a comprehensive analysis of the education sector in developing countries. Volume 1 of the guidelines discusses the context for the development of the education sector, enrollment, internal efficiency, out-of-school children, cost and financing, quality, system capacity and management, external efficiency and equity.
KerkoCite.ItemAlsoKnownAs: 2339240:JEZ8LW9X 2339240:R2HMFCUX 2405685:24DM6GFV 2405685:HCLG4ULQ

Education sector analysis methodological guidelines. Vol. 2: Sub-sector specific analysis - UNESCO-IIEP; World Bank; UNICEF; Global Partnership for Education (2019)
The purpose of these guidelines is to provide methods for comprehensive education sector analyses to support the preparation and monitoring of education sector plans. They are an update of a 1999 document that has been used to support the preparation of approximately 70 Education Country Status Reports (CSR) in more than 40 countries. The goal of the guidelines is to strengthen national capacities in order that Government teams can conduct education sector analyses with progressively less external support.
KerkoCite.ItemAlsoKnownAs: 2405685:BRN5TXIS